Incomplete Reiter's syndrome following chemotherapy of acute myeloid leukaemia. Issue 733 (November 1986) - Dharmasena, F.; Englert, H.; Catovsky, D.; Galton, D. A.; Drysdale, H. C.
Abstract : Reiter's syndrome and other reactive arthritides have been described following infection with various organisms although they can occur in unusual circumstances without an obvious infectious precipitant. We have recently witnessed two attacks of reactive arthritis and keratoderma blenorrhagica occurring in an HLA B27 adult male following chemotherapy on two separate occasions with the same drugs for acute myeloid leukaemia. No attacks occurred before or following the cessation of these drugs. This supports the view that in Reiter's syndrome a common pathogenic pathway is triggered by an 'arthritogenic factor' which in this case appears to have been chemical.